Neurological complications of varicella zoster virus reactivation: Prognosis, diagnosis, and treatment of 72 patients with positive PCR in the cerebrospinal fluid. Issue 2 (18th January 2022) - Lenfant, Tiphaine; L'Honneur, Anne‐Sophie; Ranque, Brigitte; Pilmis, Benoit; Charlier, Caroline; Zuber, Mathieu; Pouchot, Jacques; Rozenberg, Flore; Michon, Adrien
Abstract: Background: VZV infection can involve every level of the neurologic system: from the central nervous system (CNS) to the peripheral nervous system (PNS), including aseptic meningitis. Prognosis seems to differ between these neurological involvements. Prognostic factors remain unknown. Methods: This is a retrospective multicenter study including all patients with a positive VZV polymerase chain reaction (PCR) in the cerebrospinal fluid (CSF) from eight centers in Paris (France) between 2011 and 2018. Unfavorable outcome was defined as mortality linked to VZV or incomplete recovery. Modified Rankin Scale (mRS) evaluated disability before and after the infection, with the difference designated as Rankin Delta. Results: Seventy‐two patients were included (53% male, median age 51 years, median mRS 0). Immunosuppression was reported in 42%. The clinical spectrum included 26 cases of meningitis, 27 instances of CNS involvement, 16 of PNS involvement, and 3 isolated replications (positive PCR but no criteria for neurological complications from VZV). Antiviral treatment was administered to 69 patients (96%). Sixty‐two patients completed follow‐up. Death linked to VZV occurred in eight cases. Unfavorable outcome (UO) occurred in 60% and was significantly associated with a higher prior mRS (Odd‐ratio (OR) 3.1 [1.4–8.8] p  = .012) and the presence of PNS or CNS manifestations (OR 22 [4–181] p  = .001, OR 6.2 [1.3–33] p  = .03, respectively, compared to meningitis). In the CSF, higher protein level ( p  < .0001) was also significantly associated with a higher Rankin Delta. Conclusions: Neurological complications of VZV with evidence of CSF viral replication are heterogeneous: aseptic meningitis has a good prognosis, whereas presence of CNS and PNS involvement is associated with a higher risk of mortality and of sequelae, respectively. Abstract : Neurological complications of varicella zoster virus reactivation can involve the central and peripheral nervous systems. Central nervous system involvement was associated with a higher mortality and peripheral involvement with higher sequelae. Higher age and Rankin scale prior to infection were associated with a poorer prognosis.